OVERCOMING EMPTINESS IN THE TRANSLATION OF DUBRAVKA UGREŠIĆ - Olja Perišić (Filolog, 2023)
The theme of this paper concerns the main aspects of translating a linguistically and culturally hybrid text, using the example of two Dubravka Ugrešić’s books (1949–2023), Karaoke culture and Europe in Sepia. The author addresses contemporary themes in a globalised and increasingly virtual world, while constantly revisiting the Soviet and Yugoslav communist past through her personal experiences. Existing between languages and interpreting such a diverse literary world requires a profound understanding of historical, linguistic, and cultural contexts, as well as translation strategies aimed at bridging the inevitable spatiotemporal gap that arises between the two versions of the text. The main research questions are: what are the criteria for including or excluding different elements of heterolinguism/ plurilingualism in a translated text? By what linguistic means is it domesticated in a culturally and linguistically hybrid text?